Is Alzheimer’s Also a Stem Cell Disease? – The Zebrafish Perspective - Kizil, Caghan; Bhattarai, Prabesh (Frontiers in Cell and Developmental Biology, 2018)
Alzheimer’s disease (AD) is the most common neurodegenerative disease and is the leading form of dementia. AD entails chronic inflammation, impaired synaptic integrity and reduced neurogenesis. The clinical and molecular onsets of the disease do not temporally overlap and the initiation phase of the cellular changes might start with a complex causativeness between chronic inflammation, reduced neural stem cell plasticity and neurogenesis. Although the immune and neuronal aspects in AD are well studied, the neural stem cell-related features are far less investigated. An intriguing question is, therefore, whether a stem cell can ever be made proliferative and neurogenic during the prevalent AD in the brain. Recent findings affirm this hypothesis and thus a plausible way to circumvent the AD phenotypes could be to mobilize the endogenous stem cells by enhancing their proliferative and neurogenic capacity and also provide the newborn neurons the potential to survive and integrate into the existing circuitry. To address these questions, zebrafish offers unprecedented information and tools, which can be effectively translated into mammalian experimental systems.